Imaging-based machine learning to evaluate the severity of ischemic stroke in the middle cerebral artery territory - Gang Xie; Jin Gao; Jian Liu; Xuwei Zhou; Zhengkai Zhao; Wuli Tang; Yue Zhang; Lingfeng Zhang; Kang Li (BMC Medical Imaging)
Abstract Objectives This study aims to develop an imaging-based machine learning model for evaluating the severity of ischemic stroke in the middle cerebral artery (MCA) territory. Methods This retrospective study included 173 patients diagnosed with acute ischemic stroke (AIS) in the MCA territory from two centers, with 114 in the training set and 59 in the test set. In the training set, spearman correlation coefficient and multiple linear regression were utilized to analyze the correlation between the CT imaging features of patients prior to treatment and the national institutes of health stroke scale (NIHSS) score. Subsequently, an optimal machine learning algorithm was determined by comparing seven different algorithms. This algorithm was then used to construct a imaging-based prediction model for stroke severity (severe and non-severe). Finally, the model was validated in the test set. Results After conducting correlation analysis, CT imaging features such as infarction side, basal ganglia area involvement, dense MCA sign, and infarction volume were found to be independently associated with NIHSS score (P < 0.05). The Logistic Regression algorithm was determined to be the optimal method for constructing the prediction model for stroke severity. The area under the receiver operating characteristic curve of the model in both the training set and test set were 0.815 (95% CI: 0.736–0.893) and 0.780 (95% CI: 0.646–0.914), respectively, with accuracies of 0.772 and 0.814. Conclusion Imaging-based machine learning model can effectively evaluate the severity (severe or non-severe) of ischemic stroke in the MCA territory. Clinical trial number Not applicable.